# trig

posted by .

find the exact zeros of the function in the interval [0, 2π)
2 cot squared x + 3 csc x=0

• trig -

We know that
1 + cot^2 Ø = csc^2 Ø
so our equation is

2(csc^ x - 1) + 3csc x = 0
2 csc^2 x + 3csc x - 2 = 0
(2cscx -1)(cscx + 2) = 0
cscx = 1/2 or cscx = -2
or
sinx = 2 (not possible) or sinx = -1/2

so x must be in III or IV
x = 7π/6 or 11π/6

## Similar Questions

1. ### Trig

Find the exact values of the six trigonometric functions 0 if the terminal side of 0 in standard position contains the points(-5,-4). (0 is not the number zero I don't know what its called) I have to find r first. r=sqrt x^2+y^2 r=sqrt …
2. ### trig 30

For csc^2 A-1/cot A csc A, what is the simplest equivalent trig expression?
3. ### trig

FInd the exact value pf the 6 trig function of alpha Given: point (-2,-6) on the terminal side of the angle in standard position sin alpha cos alpha tan alpha sec alpha csc alpha cot alpha
4. ### Math/Trig

How would I evaluate these trig functions without using a calculator?
5. ### Trig

find all solutions to the equation √3 csc(2theta)=-2 Would the answer be π/6 + 2πn, 5π/6 +2πn or π/6 + πn, 5π/6 +πn?
6. ### Precalc/Trig

Sorry there are quite a few problems, but I just need to know if these are correct (and if they aren't, where I went wrong): 1. Solve these equations. tanθ = -√3 θ = 2π/3 + kπ θ = 5π/3 + kπ …
7. ### Trig verifying identities

I am having trouble with this problem. sec^2(pi/2-x)-1= cot ^2x I got : By cofunction identity sec(90 degrees - x) = csc x secx csc-1 = cot^2x Then split sec x and csc-1 into two fractions and multiplied both numerator and denominators …
8. ### precalc

Given that sec 3π/10 ≈ 17/10 and csc 3π/10 ≈ 17/14, find the following: 1. sin 3π/10 ≈ 14/17 (is this one correct) 2. csc 43π/10 ≈ 3. sec 2π/10 ≈ 4. cot -12π/10 ≈ 5. …
9. ### calculus

1. what trig function has an amplitue of 1 and negative values for angles between π/2 and π?
10. ### trig

verify (csc^4-1)/cot^2x=2+cot^2x So this is what I have so far on the left side (csc^2x+1)(cscx+1)(cscx-1)/cot^2x =(csc^2x+1)(cot^2x)/cot^2x i think I'm doing something wrong. Please help!

More Similar Questions